Analisis Penilaian Ergonomi Postur Kerja Ketika Memasang Roda Dengan Metode Ovako Work Posture Analysis System (Owas) Dan Rapid Entire Body Assesment (Reba) Untuk Mencegah Musculoskeleal Disorders Di Perum PPD Ciputat Jakarta - Ramadhani , Muhammad; Rukman, Rukman (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2019)
This ergonomi working posture research was done to reduce Muskuloskeletal Disorders inworking activity at put the wheel in to the position in Perum PengangkutanPenumpangDjakarta (PPD) by three workers. Workers are working in bending and crouching in longperiods of time so that it can cause Muskuloskeletal Disorders. The workers are generallypaying less attention to body posture at work. The Rapid Entire Body Assesment (REBA)method and Ovako Work Posture Analysis System (OWAS) method is used to analyze bodyposture. The research was conducted by interviewing the parties concerned at the activityput the wheel in to the position for designing the working tools required